A reprogramação da saga Harry Potter: leitura das enunciações mágicas do herói decadente - Bezerra, Diego Nunes (2012)
The best-seller Harry Potter s series, written by the British author J. K. Rowling, and stared by the character Harry Potter have been studied by the contemporaneous Criticism while the image spectacular society s concepts. Among these concepts there are the saga, and the Greek hero, as structures of the myth, and both are restructured by media mechanism action in favor of the fabled contamination. In this study, the saga occupies the center of a heroic circular action that remodels the hero concept, and also gives us the updated decadent hero while image integrated to the mass society system. In a ludic point of view, the series Harry Potter (seven books) are about sharing the hero s (Harry Potter) qualities in counterpoint to the anti-hero Voldemort, who brings us the construction of the intrigue, the effects of the dual decadent nature game: bad vs. good, once humanized by the marvelous multimidia contemporaneous element. In this way, the marvelous becomes the support roll in the adventures of this hero in the gaps created by him through the remodeling saga. Under the communicative perspective of the fanfiction, the potternian fiction corroborates to the decadent heroic structure, by using a mixture of mass reading, and mass writing into the classic saga, extended to the author-mass, and to the readermass, creating the parenthood of the modern saga. This communicative link of the reprogrammed saga made by way of magic and witchcraft element shave lead up us to the study of this central theme, in three stages: the fiction and fanfiction intertextuality in Harry Potter s series; the architext in construction: Harry Potter s series; the fiction in intertextuality: the reading of magic enunciations